Linear array CMOS detectors for laser doppler blood flow imaging - Himsworth, John M. (2011)
Laser Doppler blood flow imaging is well established as a tool for clinical research. The technique has considerable potential as an aid to diagnosis and as a treatment aid in a number of situations. However, to make widespread clinical use of a blood flow imager feasible a number of refinements are required to make the device easy to use, accurate and safe.